Carbon Nitride Materials for Water Splitting Photoelectrochemical Cells. Issue 19 (21st February 2019) - Volokh, Michael; Peng, Guiming; Barrio, Jesús; Shalom, Menny
Abstract: Graphitic carbon nitride materials (CNs) have emerged as suitable photocatalysts and heterogeneous catalysts for various reactions thanks to their tunable band gap, suitable energy‐band position, high stability under harsh chemical conditions, and low cost. However, the utilization of CN in photoelectrochemical (PEC) and photoelectronic devices is still at an early stage owing to the difficulties in depositing high‐quality and homogenous CN layer on substrates, its wide band gap, poor charge‐separation efficiency, and low electronic conductivity. In this Minireview, we discuss the synthetic pathways for the preparation of various structures of CN on substrates and their underlying photophysical properties and current photoelectrochemical performance. The main challenges for CN incorporation into PEC cell are described, together with possible routes to overcome the standing limitations toward the integration of CN materials in PEC and other photoelectronic devices. Abstract : At the coalface : The advantages, drawbacks, and prospects of using polymeric graphitic carbon‐nitride based materials as the active components in water‐splitting photoelectrochemical cells is reviewed and discussed.